The Correlation between Students' Vocabulary Achievement and Their Speaking Ability of the Twelfth Grade at MA Al-Islam Kemuja - Estriyo, Junita (EEdJ: English Education Journal, 2024)
The purposes of this study were to find out: (1) students’ vocabulary achievement, (2) students’ speaking ability, (3) whether there was any significant correlation between students’ vocabulary achievement and students’ speaking ability at MA Al-Islam Kemuja. This study applied a Pearson Product Moment formula. The population of this study were all students of the twelfth grade at Ma Al-Islam Kemuja, with the total 142 students. The total of samples were 45 students of twelfth grade at Ma Al-Islam Kemuja. The result of students’ vocabulary achievement was in good criteria. It could be seen from the result of the mean score of students’ vocabulary achievement namely 76.62. Regarding the students’ speaking ability, the findings of the study showed that the result of the mean score was 68.58 Then, the findings for the correlation between students’ vocabulary achievement and students’ speaking ability was 0.583 and the p-value (Sig. (2- tailed)) was 0.000. Meanwhile, the critical value in the table at significant (2- tailed) level 5% was 0.294. It meant that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. It could be concluded that there was significant correlation between students’ vocabulary achievement and students’ speaking ability